Effect of different levels of poultry offal concentrate and soybean meal on the growth rates of common carp larvae Cyprinus carpio (L.) - Al-Hasoon, Ahmed Shihab (Iraqi Journal of Aquaculture, 2022)
Effect of different levels of poultry offal concentrate (POC) and soybean meal (SM) on the growth rates of common carp larvae Cyprinus carpio had been studied, 360 larvae were distributed in 9 plastic 10 liter containers divided to three treatments with three replicates for each one, 40 larvae were put in every replicate (10 larvae L), the larvae were fed three diets for 35 days, the diets percentage were (25:75), (50:50) and (75:25) from (POC) and (SM) respectively. The body weight, specific growth rate, relative growth rate, feed conversion rate and survival rate were measured, it has been found that the best survival rate, relative growth rate, specific growth rate and feed conversion rate was in the 2nd treatment, it was 82 %, (77.9 ±1.22) %, (1.65 ±0.021) % and 3.0±0.1 respectively, there was a significant differences (P<0.05) between the different feeding treatments.